Peranan Planner di Devisi Operasional dalam Menangani Kegiatan Bongkar Muat Petikemas di PT. Pelindo Petikemas Belawan - Jeremias Marlindung Lumban Gaol; Dafid Ginting; Lilis Lilis (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
PT Pelindo Petikemas Belawan. is a container service company. This paper aims to determine the role of the Planner in container loading and unloading activities in the operational division engaged in container loading and unloading. To support the smooth running of loading and unloading work is greatly influenced by the role of the planner in it as well as the loading and unloading equipment facilities and procedures related to the loading and unloading. The role of the planner in operational activities is to receive emails from the shipping company (agent) then the planner immediately makes a loading list that has been sent by the shipping company to the planner with that the planner also determines the place to stack containers on the ship and regulates the equipment that operates for loading and unloading containers. In the role of the planner in loading and unloading activities, better accuracy and supervision are required, because without supervision and accuracy in loading and unloading activities, it can result in errors in exporting/importing containers and damage to the cargo to be loaded/unloaded. In writing this paper, the method used by the author in obtaining data is based on direct observation in the field related to the object, literature analysis and direct interviews.